IMPLIKASI SHARIAH GOVERNANCE TERHADAP REPUTASI DAN KEPERCAYAAN BANK SYARIAH - Siti Maria Wardayati (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2011)
The object of this study is Bank Muamalat Indonesia in Central Java, while the number of samples used was 200 respondents using purposive sampling techniques. The techniques of analysis used descriptive analysis and SEM analysis with the help of AMOS. The results of computational data show that the implementation of sharia government that consists of 6 (six) indicators, namely: transparency, accountability, responsibility, indedendency, justice and shariah compliance has shown good results. Shariah compliance is an indicator of the dominant Islamic government, while responsibility and justice is an indicator of weak governance in explaining sharia. Implementation of shariah governance significant effect on the reputation and customer confidence in Islamic banks.